2020
DOI: 10.1080/09512748.2020.1772352
|View full text |Cite
|
Sign up to set email alerts
|

‘Garuda shield’ vs ‘sharp knife’: operationalising Indonesia’s defence diplomacy

Abstract: In the Post New Order period, there was a significant development in Indonesia. The issuance of the Law on TNI in 2004, has since guided how the Indonesian military operates in dealing with external and internal security threats and curbed its socio-political role, which is associated with the New Order regime.However, it has not explicitly touched upon the implementation of defence diplomacy, which has significantly increased within the last decade. Hence, the article aims to analyse the development of Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…But their tensions between Malaysia and the Philippines (think of the recent incident in Sabah, for instance), and this constitutes a potential obstacle to closer Counter-terrorism cooperation between those two states. This opinion is related to Acharya & Acharya (2010) which found that the different perceptions of Southeast Asia countries in responding to the threat of terrorism are influenced by national constraints and how countries correlate terrorism with political-security issues.…”
Section: Effectiveness Of Indonesia's Defense Diplomacy To Promote Asean's/arf's Counter-terrorism Cooperationmentioning
confidence: 99%
See 2 more Smart Citations
“…But their tensions between Malaysia and the Philippines (think of the recent incident in Sabah, for instance), and this constitutes a potential obstacle to closer Counter-terrorism cooperation between those two states. This opinion is related to Acharya & Acharya (2010) which found that the different perceptions of Southeast Asia countries in responding to the threat of terrorism are influenced by national constraints and how countries correlate terrorism with political-security issues.…”
Section: Effectiveness Of Indonesia's Defense Diplomacy To Promote Asean's/arf's Counter-terrorism Cooperationmentioning
confidence: 99%
“…Meanwhile, for Malaysia, transnational terrorism originated from Western countries which intend to against the global Muslim community. There is an ambivalent perception about American policy that is considered as anti-Islamic and oppressing Muslims throughout the world (Acharya & Acharya, 2010). Furthermore, since Singapore relies heavily on the trade and tourism sectors, the threat of terrorism can be a major disaster for its economy.…”
Section: Effectiveness Of Indonesia's Defense Diplomacy To Promote Asean's/arf's Counter-terrorism Cooperationmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars perceive defence diplomacy as the use of military as foreign policy instrument to achieve national and foreign objectives abroad (Cottey and Forster, 2004; Drab, 2018; Edmonds and Mills, 1998). Among defence diplomacy activities, joint exercise has been identified as one of the most important activities (Cottey and Forster, 2004; Gindarsah, 2016; Laksmana, 2011; Wenas Inkiriwang, 2020a) because it can contribute to supporting defence co-operation between countries and nations (Cheyre, 2013; Muthanna, 2011; Wenas Inkiriwang, 2020a). Additionally, joint exercise is useful in improving interoperability with foreign militaries and increasing levels of trust and respect between participating countries (Muthanna, 2011; Sachar, 2003).…”
Section: Indonesia’s Defence Diplomacy and Joint Exercisesmentioning
confidence: 99%
“…Third, the article observes how Indonesia has benefitted from the MNEK as its multilateral defence diplomacy activity. Fourth, it discusses the findings by observing the four motives of defence diplomacy identified in the previous study on Indonesia’s defence diplomacy and the country’s two joint military exercises, the “Garuda Shield” and the “Sharp Knife” (Wenas Inkiriwang, 2020a). It also looks at the external, state-level, and individual-level variables, focusing on the great powers’ rivalry, role of national leaders, and institutional rivalry.…”
Section: Introductionmentioning
confidence: 96%